Definition of Naturally Processed Peptides Reveals Convergent Presentation of Autoantigenic Topoisomerase I Epitopes in Scleroderma. Issue 8 (26th June 2020) - Tiniakou, Eleni; Fava, Andrea; McMahan, Zsuzsanna H.; Guhr, Tara; O'Meally, Robert N.; Shah, Ami A.; Wigley, Fredrick M.; Cole, Robert N.; Boin, Francesco; Darrah, Erika
Abstract : Objective: Autoimmune responses to DNA topoisomerase I (topo I) are found in a subset of scleroderma patients who are at high risk for interstitial lung disease (ILD) and mortality. Anti–topo I antibodies (ATAs) are associated with specific HLA–DRB1 alleles, and the frequency of HLA–DR–restricted topo I–specific CD4+ T cells is associated with the presence, severity, and progression of ILD. Although this strongly implicates the presentation of topo I peptides by HLA–DR in scleroderma pathogenesis, the processing and presentation of topo I has not been studied. Methods: We developed a natural antigen processing assay (NAPA) to identify putative CD4+ T cell epitopes of topo I presented by monocyte‐derived dendritic cells (mo‐DCs) from 6 ATA‐positive patients with scleroderma. Mo‐DCs were pulsed with topo I protein, HLA–DR–peptide complexes were isolated, and eluted peptides were analyzed by mass spectrometry. We then examined the ability of these naturally presented peptides to induce CD4+ T cell activation in 11 ATA‐positive and 11 ATA‐negative scleroderma patients. Results: We found that a common set of 10 topo I epitopes was presented by Mo‐DCs from scleroderma patients with diverse HLA–DR variants. Sequence analysis revealed shared peptide‐binding motifs within the HLA–DRβ chains of ATA‐positive patients and a subset of topo I epitopes with distinct sets of anchor residues capable of binding to multiple different HLA–DR variants. The NAPA‐derived epitopes elicited robust CD4+ T cell responses in 73% of ATA‐positive patients (8 of 11), and the number of epitopes recognized correlated with ILD severity ( P = 0.025). Conclusion: These findings mechanistically implicate the presentation of a convergent set of topo I epitopes in the development of scleroderma.